Tradisi Pembuangan Ayam Jawa di Jembatan Kali Progo oleh Keluarga Pengantin dalam Perspektif Urf - Laela Qodriyah; Sumarjoko Sumarjoko; Hidayatun Ulfa (Jurnal Iqtisad, 2022)
Abstract The throwing of chickens at Kali Progo bridge by the bride and groom's families is one of the traditional Javanese wedding ceremony traditions that we still see in Jombor Village. When the bridal procession's second journey passes through a large river, this tradition is carried out. The purpose of this research is to learn about Urf tradition of dumping chickens at Kali Progo bridge by the bride's family, as well as the origins of this tradition. This qualitative study examines and directly observes the lives of people who still practice historical, anthropological, and Islamic legal approaches. Data collection techniques were used to collect primary data from interviews with traditional leaders, religious leaders, and residents of Jombor Village who still practice this tradition. Books, documents, journals, and other secondary data sources were used, and they were then analyzed using descriptive methods. The findings of the study show that Islam forbids the belief that throwing away chickens will provide safety, because Allah SWT is the only one who can provide salvation. The urf aspect, which is based on syara' and the framework of ushul fiqh, also states that it is not permissible to do so, because this tradition includes urf fasid, which are actions that are not in accordance with the Quran and hadith or make the group's journey to difficult location. Furthermore, this tradition wastes previously discarded chickens. Keywords: Tradition; Java Chicken; Urf